Analysis of the relationship between the enterprise and the environment in the context of managing the relational capital = Analiza relacji przedsiębiorstwa z otoczeniem w kontekście zarządzania kapitałem relacyjnym - Walecka, Anna (Zielona Góra: Faculty of Economics and Management Press)
The aim of the paper is to present how important is the management of relational capital and present the results of empirical research constituting a part of a pilot study on relational capital management by Polish enterprises. They were conducted among managers of 82 enterprises operating in Poland. The research method was the diagnostic survey method (technique of the distributed questionnaire).
Keywords: kapitał relacyjny przedsiębiorstwa; zarządzanie kapitałem relacyjnym; interesariusze; relational capital; RC management; stakeholders